5. Adaptive radiotherapy: methods and tools. (December 2016) - Lafond, C.; A. Simon,; Henry, O.; Perichon, N.; Castelli, J.; Acosta, O.; De Crevoisier, R.
Abstract : Anatomical and/or biological changes occurring during radiotherapy course modify delivered dose to the patient requiring an adaptation of the treatment especially in case of intensity modulated Radiotherapy (IMRT). Adaptive radiotherapy (ART) has been introduced when several plans are used to treat a patient during radiotherapy. Adaptation may be performed online, offline or in a hybrid way. The implementation of RTA in routine use requires the automating of the entire process: decision criteria, segmentation, planning, validation and quality control. An automated process should allow a fast and fluid implementation to limit the increase of workload but especially to ensure the quality and safety of treatments. New images of the patient are needed for ART to perform many process: image registration, segmentation and evaluation of cumulative dose. Deformable image registration methods are generally used to image registration and contours propagation. Fraction and cumulative dose evaluations use deformable image registration methods or more complex methods based on Monte Carlo calculation. These methods have uncertainties and have to be evaluated. However evaluation and validation tools are still being developed. The physicist mission is to ensure that every new technology, as RTA, is deployed with highest safety by technical validation and by implementing a specific quality assurance program. RTA implementation still raises many questions, so its potential clinical application requires great caution and should be carefully explored in prospective clinical trials. It requires close collaboration between oncologists, medical physicists, expert engineers in image processing and equipment manufacturers.